The effect of the gas–solid contacting pattern in a high-temperature thermochemical energy storage on the performance of a concentrated solar power plant. Issue 4 (8th February 2016) - Ströhle, S.; Haselbacher, A.; Jovanovic, Z. R.; Steinfeld, A.
Abstract : This work presents a framework for comparing reactor concepts for thermochemical storage and analyzing their impact on the performance of CSP plants. Abstract : This work investigates how the gas–solid contacting pattern in a thermochemical energy storage system charged and discharged by air as the heat-transfer fluid influences (1) the integration of the storage into a concentrated solar power plant and (2) the performance of the power plant. The investigation uses 6Mn2 O3 ↔ 4Mn3 O4 + O2 as the model reaction taking place in packed- and fluidized-bed reactors simulated based on idealized contacting patterns and empirical reduction/oxidation rate laws. Considering computed heat-transfer fluid outflow temperatures and the operating requirements by the power block and the solar field, the preferred integration into the power plant is identified to be parallel for the packed bed and serial for the fluidized bed. A more detailed comparison of these two plant configurations shows that a parallel integration of a well-designed storage system is advantageous due to the increased power block inlet temperatures and the absence of limitations on the attainable duration of discharging. Furthermore, combining thermochemical and sensible energy storage systems in one storage unit is beneficial for the parallel integration of a batch-type storage system because it merges increased volumetric and gravimetric storage densities provided by the thermochemical section with reduced outflow temperatures during charging provided by a low-cost sensible section.